Trends in the numbers of SARS-CoV-2 infections among students: a prospective cohort study comparing students in sports boarding schools with students in day schools during early COVID-19 pandemic - Barsch, Friedrich; Peters, Vera; Morath, Oliver; Krumnau, Oliver; Maier, Philipp; Huzly, Daniela; Prettin, Stephan; Deibert, Peter (Frontiers in Public Health, 2023)
During the first months of the Covid pandemic it emerged that facilities where people gather or live together in cohorts, such as nursing homes or schools, were particularly at high risk for becoming hotspots of virus transmission. German political and health institutions responded with far-reaching interventions and preventive strategies to protect the population from infection with SARS-CoV-2. In this context, it remains unclear whether boarding schools for sports particularly pose a risk of infection to their residents. In a single-center prospective cohort study, numbers of SARS-CoV-2 infections of students in sports boarding schools (n = 11) versus students attending regular day schools (n = 22) in the region Freiburg/Hochschwarzwald in Germany were investigated over a period from October 2020 to January 2021 via regular virus and antibody screening (German Clinical Trials Register; Study ID: DRKS00021909). In addition, individual and behavioral risk factors for infection were stratified via questionnaire, which provide an indication of cohort specific risk factors for infection and the success of the implementation of hygiene concepts, as well as other infection prevention strategies, within the respective facilities. Regarding SARS-CoV-2 infection numbers, the screening detected no significant group difference between sports boarding schools versus day schools. The study results provide indications that sports boarding schools did not pose an increased risk of infection, assuming that the facilities prevent virus transmissions with appropriate preventive strategies and hygiene measures. In future pandemic scenarios larger-scale and multicenter studies are necessary to achieve more comprehensive epidemiological data in this field.